Upaya Meningkatkan Hasil Belajar Murid Kelas VI Materi Lingkaran Pelajaran Matematika Melalui Penggunaan Metode Every On E Is A Teacher Here Pada SD Negeri Ie Leubeue Kecamatan Kembang Tanjong Kabupaten Pidie - Darlina (Journal of Technology and Literacy in Education, 2022)
This study aims to improve the results of learning mathematics in circle material as well as for students of class VI at SD Negeri Ie Leubeue, Kembang Tanjong District, Pidie Regency, for the 2019/2020 academic year. This research is a class action research (action research). The subjects of this study were 20 grade VI students of SD Negeri Ie Leubeue, Kembang Tanjong District, Pidie Regency. The results of this study indicate that: Through the use of the Every One Is A Teacher Here method in classroom action research at SD Negeri Ie Leubeue there has been an increase in student learning outcomes in mathematics, especially Circle material. Before learning was carried out using the Every One Is A Teacher Here method, the student’s score was 54. In the first cycle, the evaluation results of the students obtained an average score at the first meeting was 60, and at the second meeting, 60.50. Whereas in cycle II it continued to increase to an average of 67.50 at the 1st meeting and 78.00 at the 2nd meeting. From this study there was a significant increase in learning completeness from cycle I to cycle II by 20%, because the mastery in cycle I was only 70%, but in cycle II it reaches 90%, meaning that there is an increase in student learning outcomes and process activities.